Pedagogik Ekonomi Syariah dalam Islam - Maryati Maryati (Al-Tafaqquh: Journal of Islamic Law, 2021)
Islamic economics pedagogically is a system of knowledge that studies economic problems. The implementation of this system applies Islamic law. As a prototype system that has its own characteristics, Islamic economics is applied based on the Qur'an, As-Sunnah, Ijtima', and Ijtihad/Qiyas. Its implementation is carried out following the principles; (1) Tawhid and Brotherhood, (2) Work and Productivity; and (3) Fair Distribution of Wealth. The objective of sharia economics is to meet the basic needs of mankind based on Islamic values. Islamic economics is not only a practical system, but also a pedagogical system of knowledge that contributes to knowledge and enlightenment of the economic system. The main challenge of the Islamic economic system lies in its epistemological and terminological problems which are still interpreted as mere normative doctrines of the Islamic religion. The Islamic economic system in today's contemporary era must be able to interpret its existence as a science that becomes a humanist alternative for the inequalities of the failed global economic system and is able to establish the system as a pedagogic